Comparison of the effects of nitrogen-, sulfur- and combined nitrogen- and sulfur-deprivations on cell growth, lipid bodies and gene expressions in Chlamydomonas reinhardtii cc5373-sta6 - David I. Gonzalez; Ruby A. Ynalvez (BMC Biotechnology, 2023)
Abstract Background Biofuel research that aims to optimize growth conditions in microalgae is critically important. Chlamydomonas reinhardtii is a green microalga that offers advantages for biofuel production research. This study compares the effects of nitrogen-, sulfur-, and nitrogen and sulfur- deprivations on the C. reinhardtii starchless mutant cc5373-sta6. Specifically, it compares growth, lipid body accumulation, and expression levels of acetyl-CoA carboxylase (ACC) and phosphoenolpyruvate carboxylase (PEPC). Results Among nutrient-deprived cells, TAP-S cells showed significantly higher total chlorophyll, cell density, and protein content at day 6 (p < 0.05). Confocal analysis showed a significantly higher number of lipid bodies in cells subjected to nutrient deprivation than in the control over the course of six days; N deprivation for six days significantly increased the size of lipid bodies (p < 0.01). In comparison with the control, significantly higher ACC expression was observed after 8 and 24 h of NS deprivation and only after 24 h with N deprivation. On the other hand, ACC and PEPC expression at 8 and 24 h of S deprivation was not significantly different from that in the control. A significantly lower PEPC expression was observed after 8 h of N and NS deprivation (p < 0.01), but a significantly higher PEPC expression was observed after 24 h (p < 0.01). Conclusions Based on our findings, it would be optimum to cultivate cc5373-sta6 cells in nutrient deprived conditions (-N, -S or –NS) for four days; whereby there is cell growth, and both a high number of lipid bodies and a larger size of lipid bodies produced.